Keeping the Listener Engaged: A Dynamic Model of Bayesian Persuasion - Che, Yeon-Koo; Kim, Kyungmin; Mierendorff, Konrad (Journal of Political Economy, 2023)
We consider a dynamic model of Bayesian persuasion in which information takes time and is costly for the sender to generate and for the receiver to process, and neither player can commit to their future actions. Persuasion may totally collapse in a Markov perfect equilibrium of this game. However, for persuasion costs sufficiently small, a version of a folk theorem holds: outcomes that approximate Kamenica and Gentzkow’s sender-optimal persuasion as well as full revelation and everything in between are obtained in Markov perfect equilibrium as the cost vanishes.